On the Relationship Between EB-3 Profiles and Microtubules Growth in Cultured Cells - Urazbaev, Arshat; Serikbaeva, Anara; Tvorogova, Anna; Dusenbayev, Azamat; Kauanova, Sholpan; Vorobjev, Ivan (Frontiers in Molecular Biosciences, 2021)
Microtubules are dynamic structures undergoing rapid growth and shrinkage in living cells and in vitro. The growth of microtubules in vitro was analyzed with subpixel precision (Maurer et al., 2014), however, to what extent these results could be applied for microtubules growing in vivo remains largely unknown. Particularly, the question is whether microtubule growth velocity in cells could be sufficiently approximated by a Gaussian distribution or its variability requires a more sophisticated description? Addressing this question, we used time-lapse microscopy and mathematical modeling we analyzed EB-3 comets forming on microtubules of cultured cells with subpixel precision. Parameters of comets (shape, form, and velocity) were used as topological characteristics of 3D voxel objects. Using regression analysis, we determined the real positions of the microtubule tips in time-lapse sequences. By exponential decay fitting of the restored comet intensity profile, we found that in vivo EB-3 rapidly exchanges on growing microtubule ends with decoration time ~ 2 s. We next developed the model showing that the best correlation between comet length and microtubule end growth velocity is at time intervals close to the decoration time. In the cells, EB comet length positively correlates with microtubule growth velocity in preceding time intervals, while demonstrating no correlation in subsequent time intervals. Correlation between comet length and instantaneous growth velocity of microtubules remains under Nocodazole treatment when mean values of both parameters decrease. Our data show that the growth of microtubules in living cells is well approximated by a constant velocity with large stochastic fluctuations.